Mediating Social Media: Examining User Risk Perception on Facebook - Borbey, Daniel (Université d'Ottawa / University of Ottawa, 2010)
This thesis explores how social networking sites are changing the way individuals socialize in everyday life, and how users mediate this social media. The hypothesis explored is that Facebook user’s perception of risk, when using the site, is related to how they frame the technology. Drawing on conceptual and theoretical tools from science studies and the sociologies of friendship, risk and surveillance, interview data is collected and analysed in order to identify the dynamics that structure Facebook use. It is concluded not only that, as hypothesized, participant’s awareness and perception of risk is based upon their framing of the social networking technology, but also that the framing processes arise from the technosocial hybrid nature of Facebook. That is to say, it is not exclusively based on technological possibility or on existing social practices but instead by a constant balance between the two.
Keywords: Social Networking Sites; Surveillance; Friendship; Techoscience; Risk Perception; Facebook